Cholesterol in islet dysfunction and type 2 diabetes - Brunham, Liam R. (American Society for Clinical Investigation, 2008)
Type 2 diabetes (T2D) frequently occurs in the context of abnormalities of plasma lipoproteins. However, a role for elevated levels of plasma cholesterol in the pathogenesis of this disease is not well established. Recent evidence suggests that alterations of plasma and islet cholesterol levels may contribute to islet dysfunction and loss of insulin secretion. A number of genes involved in lipid metabolism have been implicated in T2D. Recently an important role for ABCA1, a cellular cholesterol transporter, has emerged in regulating cholesterol homeostasis and insulin secretion in pancreatic β cells. Here we review the impact of cholesterol metabolism on islet function and its potential relationship to T2D.